Gender, Populism and Jacinda Ardern - Curtin, Jennifer; Greaves, Lara (A Populist Exception? : The 2017 New Zealand General Election / Edited By Jack Vowles and Jennifer Curtin., 2020)
Keywords: Elections & referenda; New Zealand; authoritarianism; elections; inclusivity; politics; populism; vote choice

Chapter 3: Citizenship Education: Rangatahi Electoral Participation - Tawhai, Veronica (Mana tangata politics of empowerment, 2011)
This is a collection of papers by senior Maori academics who are experts and have considerable mana in their chosen fields. The ten contributing authors, who are academics at Massey University, discuss the Maori language, marae, religion, the Treaty of Waitangi, the State and Maori, citizenship education, mental health, the health workforce, kaitiakitanga and horticulture. The book discusses Maori development and contemporary issues concerning Maori, both from the authors' perspectives and across different disciplines.
Keywords: elections; rangatahi; tiriti o waitangi/treaty of waitangi; voting

Standing for Mana - Cleave, Peter (Campus Press, 2012)
Keywords: elections; government; government relations; kāwanatanga; mana party; parliament; political activity

A Permanent Expedient? MMP and Māori Politics - Keenan, Danny (He Pukenga Korero: a journal of Māori studies, 1996)
Keywords: elections; government; kāwanatanga; mātauranga māori; representation; social life and customs; tāngata whenua

Chapter 7: The Treaty of Waitangi and Social Well-being: Justice, Representation, and Participation - Sullivan, Ann (Waitangi Revisited, 2005)
Keywords: crown; elections; government relations; history; land tenure; local government; māori electorates; māori seats; parliament; race relations; social justice; tiriti o waitangi/treaty of waitangi; treaty principles; voting

Chapter Thirteen: New Māori Politics 1990s-2000s - Bargh, Maria (Huia histories of Māori: ngā Tāhuhu Kōrero, 2012)
"Collection of 17 essays from Māori scholars which cover customary law, ancestral law, the natural world, Māori urban protest, health, politics, and customary language and expression"--Publisher's information.
Keywords: elections; government relations; history; iwi; iwi chairs forum; kāwanatanga; mana party; māori electorates; māori seats; social conditions; te pāti māori; tikanga | indigenous law; tāngata whenua; voting

Mana Maori Motuhake: Maori Self-Determination - Levine, Hal; Henare, Manuka (Pacific Viewpoint, 1994)
Keywords: elections; he whakaputanga; land loss; mana motuhake; tino rangatiratanga; tiriti o waitangi/treaty of waitangi; urbanisation; waitangi tribunal

The Māori Electoral Option: How can trends in roll choices be explained? - Bargh, Maria (MAI Journal: A New Zealand Journal of Indigenous Scholarship, 2020)
The Mäori Electoral Option is a period of 4 months, every 5 years, when Mäori electors can choose whether to be on the Mäori or the General Electoral Roll. The outcome of the Mäori Electoral Option is a key factor in determining the number of Mäori seats in the New Zealand Parliament. The Electoral Commission estimates that approximately 6,000 Mäori voters each year request to change electoral roll, but in 2017 over 19,000 voters applied to change. Why were so many more Mäori wanting to change and why did they not know they could only change during the Mäori Electoral Option held every 5 years? The following year, the 2018 Mäori Electoral Option saw the first net increase of Mäori changing to the general roll since 1996. This article uses data gathered from the results of Mäori Electoral Options 1991–2018, an anonymous survey, and evaluations of Mäori Electoral Option campaigns to consider how the shifting trends in roll choices might be explained.
Keywords: elections; kāwanatanga; māori electorates; māori seats; voting

Māori and the 2017 General election: party, participation, and populism - Greaves, Lara; Hayward, Janine (A Populist Exception? The 2017 New Zealand General Election, 2020)
Keywords: elections; kāwanatanga; māori electorates; māori seats; political participation; political parties; te pāti māori; voter turnout

Indigenous Participation in Elective Bodies: The Maori in New Zealand - O'Sullivan, Dominic; Xanthaki, Alexandra (International Journal on Minority and Group Rights, 2009)
The article argues that Maori political participation in New Zealand constitutes a positive example of how the current international standards on indigenous political participation can be implemented at the national level. Notwithstanding the weaknesses of the system and the challenges laying ahead, the combination of the Mixed Member Proportional electoral system, dedicated Maori seats and the establishment of the Maori Party have ensured a Maori voice in Parliament and have broadened the possibilities of effective indigenous participation in the political life of the state. Such state practice that implements the 2007 UN Declaration on the Rights of Indigenous Peoples firmly confirms the position of the Declaration within current international law.
Keywords: UNDRIP; elections; electorates; government; indigenous rights; mmp electoral system; political participation; te pāti māori

Kei a koe te tikanga - it's your choice; The history of the Māori seats - Mulholland, Malcolm (Karaka (Christchurch, N.Z.), 2006)
Notes that the five-yearly Maori Electoral Option, during which Maori voters may chose to be on either the general or Maori electoral rolls, runs f...
Keywords: elections; government; māori electorates; māori seats

Challenges on the path to Treaty-based Local Government relationships - Bargh, Maria (Kōtuitui: New Zealand Journal of Social Sciences Online, 2021)
In this article I examine some of the challenges for Māori and Local Government on the path to Treaty-based Local Government relationships. I suggest significant challenges exist in three core areas. The first relates to the attitudes towards the ideas of Treaty-based Local Government and evident in common terminology which has a narrow focus on the identity of Māori as ‘representatives' rather than ‘Treaty partners’. The second area of challenge is in having Māori wards/constituencies established which, when they are established, are symbolically the beginnings of an acknowledgment of Treaty obligations and relationships. The third challenge is the lack of good data which limits understandings of Māori involvement in Local Government. In the second part of the article I ask whether any specific challenges can be seen that might impact on Treaty-based relationships in regard to Māori involvement as candidates and voters in Local Government elections.
Keywords: elections; local elections; local government; māori electorates; tiriti o waitangi/treaty of waitangi; treaty obligations; treaty-based relationships; voting

How the Māori Party defied expectations at the 2020 election - Morgan, Ella; Greaves, Lara (Politics in a pandemic: Jacinda Ardern and New Zealand's 2020 election, 2021)
Is this the springboard for a bigger resurgence in 2023?
Keywords: elections; electorates; labour party; parliament

‘Colonised by a rich pākehā’: the metaphorical characterisation of the Internet Mana alliance - Peters, Rachel; Hocking, Darryl (Media International Australia, 2022)
In 2014, the Internet Mana alliance unsuccessfully ran in the New Zealand general election gaining just 1.42% of the party vote and failing to secure an electorate seat. The leaders of the alliance attributed their poor election result to the narratives constructed by the mainstream media, which they believed negatively influenced the public?s perception of Internet Mana. This study agrees that the mainstream media was complicit in the alliance?s poor election result, and drawing upon the discourse dynamics framework for metaphor analysis, it shows how these potentially damaging public narratives were predominantly constituted through complex sets of systematic metaphors which together created broader schematic frames or conceptual scenarios and carried certain evaluative and attitudinal perceptions. This analysis shows how systematic metaphors such as the internet mana alliance is a marriage of convenience and the internet mana alliance is a colonial trade were used to construct a negative public narrative.
Keywords: colonisation; elections; mainstream media; political parties

The geography of deprivation in New Zealand by electorate - Exeter, Daniel J.; Crengle, Sue; Cavadino, Alana; Greaves, Lara; Zhao, Jinfeng; Lee, Arier; Browne, Michael (Kōtuitui: New Zealand Journal of Social Sciences Online, 2018)
In the run-up to the 2017 General Election, the economy, housing, health, education, inequality and justice were important policy issues. General Elections are a time when voters exercise their democratic right to vote for their preferred party and parliamentary candidate to represent themselves, their whānau and community. In many cases, political parties’ policies seek to improve the wellbeing of people who are living in more deprived communities, but people in deprived communities are typically less likely to vote. The recently released New Zealand Index of Multiple Deprivation (IMD) enables users to explore deprivation in electorates across the country. This paper compares the distribution of deprivation and voter turnout across a selection of General Electoral Districts (GEDs) and demonstrates that while overall patterns of deprivation may be similar between GEDs, the drivers of these patterns can differ immensely.
Keywords: Inequity; disparities; elections; electorates; voter turnout